Odpowiedzi

2009-12-03T18:55:10+01:00
2x + y = 9
5x - 4y = 3

y = 9 - 2x
5x - 4 * (9 - 2x) = 3

y = 9 - 2x
5x - 36 + 8x = 3

y = 9 - 2x
5x + 8x = 3 + 36

y = 9 - 2x
13x = 39

y = 9 - 2x
x = 39 : 13 = 3

y = 9 - 2 * 3 = 9 - 6 = 3
x = 3
1 5 1
  • Użytkownik Zadane
2009-12-03T18:56:52+01:00
2x+y=9 => y=9-2x
5x-4y=3

5x-4(9-2x)=3
5x-36+8x=3
13x=39 /13
x=3

y=9-2(3)
y=3
1 5 1
2009-12-03T18:58:57+01:00
2x + y = 9
5x - 4y = 3
y = 9 - 2x
5x - 4 * (9 - 2x) = 3
y = 9 - 2x
5x - 36 + 8x = 3
y = 9 - 2x
5x + 8x = 3 + 36
y = 9 - 2x
13x = 39
y = 9 - 2x
x = 39 : 13 = 3
y = 9 - 2 * 3 = 9 - 6 = 3
x = 3
1 5 1